Ant–hemipteran association decreases parasitism of Phenacoccus solenopsis by endoparasitoid Aenasius bambawalei. (10th September 2019) - Xu, Chong; Li, Qiuling; Qu, Xiaobin; Chen, Jian; Zhou, Aiming
Abstract : 1. Mutualism between ants and honeydew‐excreting hemipterans is ubiquitous in the ecosystem. It is widely accepted that ant tending facilitates the colony growth of hemipterans by protecting them from predators and parasitoids. However, few studies have explored how ant tending helps defend against natural enemies. 2. Ghost ant Tapinoma melanocephalum and the invasive mealybug Phenacoccus solenopsis have a close mutual relationship. Previous studies have shown that ghost ant tending can definitely reduce parasitism and visit frequency of Aenasius bambawalei, the dominant endoparasitoid of P. solenopsis . However, the ghost ant workers seldom attack the parasitoids. It is still unclear how the ghost ant adversely affects parasitoids. This study explored the mechanism underlying the impacts of ants on natural enemies of the mealybugs. 3. Honeydew produced by P. solenopsis was an attractant to A. bambawalei . Parasitoids exhibited less searching activity, shorter longevity and lower parasitism when supplied with less honeydew. Aenasius bambawalei showed significant avoidance of pygidial gland secretions and visual cues of ghost ants. Parasitism in plants treated with 6‐methyl‐5‐hepten‐2‐one, actinidine, and gland extracts was significantly lower than that in plants treated only with solvents (paraffin oil or double‐distilled water). 4. It is concluded that honeydew consumption by ghost ants could negatively influence the performance of parasitoids. The pygidial gland secretions and visual cues of ghost ants also significantly inhibit the parasitism. These results may contribute to a better understanding of the regulation mechanism in ant–hemipteran–enemy interactions. Abstract : Aenasius bambawalei showed a strong preference for honeydew produced by Phenacoccus solenopsis . Aenasius bambawalei exhibited less searching activity, shorter longevity and lower parasitism when supplied with less honeydew. Aenasius bambawalei showed significant avoidance of pygidial gland secretions and visual cues of Tapinoma melanocephalum . Parasitism in plants treated with these cues of ghost ants was significantly lower than in controls.